2020
DOI: 10.1136/bmjopen-2019-034377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutrition education on nutritional knowledge and intentions towards nutritional counselling in Dutch medical students: an intervention study

Abstract: ObjectiveManagement of diet-related chronic diseases may benefit from improved nutrition education of medical students. This study aims to investigate the effects of a nutrition education course on nutritional knowledge and intentions towards nutritional counselling in Dutch medical students.DesignThis is a pre–post intervention study with a comparison group. Participants completed self-reported questionnaires on nutritional knowledge and intentions towards nutritional counselling.ParticipantsIn total, 118 med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
2
32
0
1
Order By: Relevance
“…Only one study reported the costs of cooking materials, and license for Tulane’s culinary medicine curriculum [ 38 ]. While previous studies have attempted to address this gap in the literature by directly inviting program directors to comment on program costs/funding among other aspects, the majority of directors elected to provide approximate round figures without further cost breakdown, or simply elect to classify program cost as confidential [ 7 ]. Regardless of cost–benefit or cost-effectiveness analyses, lack of reporting for simple expenditures in most interventions makes it challenging to assess whether culinary medicine initiatives can be integrated into existing medical programs as the costs associated with personnel, facilities and equipment/consumables may vary significantly between programs and location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study reported the costs of cooking materials, and license for Tulane’s culinary medicine curriculum [ 38 ]. While previous studies have attempted to address this gap in the literature by directly inviting program directors to comment on program costs/funding among other aspects, the majority of directors elected to provide approximate round figures without further cost breakdown, or simply elect to classify program cost as confidential [ 7 ]. Regardless of cost–benefit or cost-effectiveness analyses, lack of reporting for simple expenditures in most interventions makes it challenging to assess whether culinary medicine initiatives can be integrated into existing medical programs as the costs associated with personnel, facilities and equipment/consumables may vary significantly between programs and location.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in culinary medicine has rapidly increased among many medical schools across the United States and other countries as a potentially low-cost, high impact strategy to equip students with practical nutrition skills that can be employed for nutrition care in clinical settings [ 5 ]. Several pilot culinary medicine programs have occurred [ 5 ] which theorise that culinary medicine initiatives completed in undergraduate medical programs may produce doctors that feel more confident providing nutrition care to their patients [ 6 , 7 ]. These programs have demonstrated significant and positive impact on medical student’s attitudes, knowledge, and competencies with practical, hands-on culinary skills and nutrition knowledge, which ultimately supports their patient counseling [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent feasibility study published online demonstrated the potential of a 3-hour, online, self-paced nutrition course administered to medical residents to result in a significant and sustained increase in nutrition knowledge and positive attitudes about the role of nutrition in clinical practice (Shafto et al, 20020). In the same context, Self-reported nutritional knowledge and intentions towards nutritional counselling, including attitude, self-efficacy and social support have been increased significantly among physicians after being exposed to a Self-reported nutritional knowledge and intentions towards nutritional counselling, including attitude, selfefficacy and social support (Coppoolse et al, 2020).…”
Section: Knowledge Statements Among Physiciansmentioning
confidence: 92%
“…Unhealthy selection of food, inadequate information on the importance of food and food groups, malnutrition and its consequences and lack of a kitchen garden among adolescents can increase the burden of malnutrition, which can be mitigated through health education intervention. Previous studies have revealed that health education intervention lays a foundation for the improvement of nutritional knowledge and attitudes relevant to healthy living [ 1 , 15 , 16 , 17 ]. Addressing the root causes of malnutrition requires a common understanding of the problems and the possible solutions therein, health education intervention across all age groups, both in school and out of school, and the political will in terms of governance, implementation and alignment of policies [ 8 ].…”
Section: Introductionmentioning
confidence: 99%